Timing of transitions, their patterns, and antecedents from emerging to established adulthood in the context of a changing society - Millová, Katarína (Psihološka obzorja (Ljubljana), 2023)
This study focuses on life transition patterns and their psychosocial antecedents in a cohort of established adults who grew up during major macrosocial changes in the Czech society. The Generation 2020 longitudinal study followed former university students since 2007. The first wave occurred when the students were 18-32 years old; the second wave occurred when they were 29-43 years old. In the first wave, they completed questionnaires on identity styles, emotional control, and self-efficacy (in terms of perceived control). In the second wave, they completed the Life History Calendar, focusing on the timing of major life transitions: moving from the parental home, entry into cohabitation, marriage, parenthood, and regular employment. Latent class analysis revealed four patterns of life transitions: work-oriented singles, normative timing, family-oriented, and work-oriented group with delayed partnership and family. Further analysis showed that emotional control and self-efficacy were not related to any pattern of life transitions, but several identity styles were significant predictors, particularly for patterns related to the early timing of marriage and family. The results indicate a certain change in the patterns of life transitions compared to older age cohorts and the importance of self-concept for later psychosocial functioning.
Keywords: adulthood; control; identiteta; identity; life transitions; macrosocial change; makrosocialne spremembe; nadzor; odraslost; življenjski prehodi